Types of EU Law Application in the Jurisprudence of the Constitutional Court of the Republic of Lithuania - Griciūnas, Paulius (Teisė, 2018)
[abstract and summary in English; full article and abstract in Lithuanian] The significance of European Union law application in the jurisprudence of the Constitutional Court of the Republic of Lithuania varies. The European Union law application in the jurisprudence of the Constitutional Court of the Republic of Lithuania is examined. The typology and categories are proposed in the research and the characteristics of each of the categories are analysed. Summary The influence of the EU law on the Lithuanian Constitutional Court (Konstitucinis Teismas, hereinafter – Constitutional Court) is analysed in this article. Research is based on a coherent analysis of the jurisprudence of the Constitutional Court. To estimate the possible influence, all the jurisprudence was analysed and all decisions (63) which refer to the EU law were identified. Any attempt to assess the jurisprudence based on an objective criterion (such as time periods of court activities, reference to written law or jurisprudence, sources of the EU law, etc.) failed. The only possible criterion which could bring substantial results would be the cases where the Lithuanian Constitutional Court refers to the European Court of Justice for a preliminary ruling. Since there is one case from 2007 for such a reference and a second from 2017, this criterion could not yet be qualified as valid due to the insufficient practice. The research proves that the influence of the EU law on the jurisprudence of the Constitutional Court could not be assessed by any objective criteria. The research continues by searching for any possibility based on subjective criteria (although ensuring a highest level of objectivity and neutrality). This assessment was based on a tailor-made methodology: all the related jurisprudence (63 decisions) was analysed and preliminary categories were identified. Then all these decisions were meticulously reassessed and assigned into one of the categories. Three categories were proposed based on the ascension of the intensity of the said influence: orienting, reinforcing and harmonising. The more intense the EU law influence, the less jurisprudence could be assigned to a certain category: 40 decisions fall within the category of orienting category, 18 decisions to reinforcing category and only 5 decisions to harmonising category. The more intensive the EU law influence is identified, the more thorough analysis has been carried out. In the category of 5 influenced decisions, the decision of the Constitutional Court to refer for a preliminary ruling is assigned (another decision is expected due to the second referral in the end of 2017). There is a brief analysis of two particular decisions based on acte claire doctrine where the Constitutional Court could have referred for a preliminary ruling. One particular case might bring some challenges due to the differences in construing the EU law by the Constitutional Court and the European Court of Justice regarding the compulsory insurance against civil liability in respect of the use of motor vehicles. The research illustrates that the Constitutional Court clearly maintains a friendly approach vis a vis EU law and the preliminary ruling procedure could be used more frequently to maintain the judicial dialogue between the highest judicial institutions of different legal systems. This attitude becomes more important when the EU law influence is clearly present in a particular case.